Information seeking behavior of Filipino visual artists - Casco, Bienvenida P.; Pascua-Cruz, Ma. Divina A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
This study was conducted to determine if Filipino visual artists make essential use of libraries; the type of libraries which would best meet their needs; their sources of information regarding (1) technological information needs, (2) visual information needs and, (3) inspirational information needs; if they make essential use of interpersonal sources regarding information in the local art scene; and their modes of selling works, procure commissions and learn about shows.
One hundred fifty respondents were selected with the use of systmatic random sampling. The respondents came from a population of 262 professional artists members of the National Commission on Culture and the Arts (NCCA); Art Association of the Philippines (AAP); and the Cultural Center of the Philippines Directory of Visual Artists. The data were gathered using a questionnaire patterned after Cobbledick's (1996) interview questionnaire. Only 82 (54.06 percent) were returned for analysis. Descriptive statistics were mainly used in the analysis.
The profile of the respondents shows that almost one-fourth (21.95 percent) of the respondents are in the 31-35 age group. Having not much difference in years of experience were age groups of 10 years and below (31.10 percent) and the 11-20 years (32.13 percent). Almost two-thirds (68.28 percent) of the respondents were able to have a bachelor's degree in Fine Arts, with more than half (58.53 percent) who are self-employed.
From the results of the study, it is concluded that artists make essential use of libraries since all of the respondents often go to the libraries. Almost half (43.39 percent) go to university and/or college libraries. Interpersonal sources or people in their own league were their sources of information regarding technology, developments in the local art scene and in the procurement of commissions. Visual information came from the respondents' own imagination (13.15 percent). Personal life experiences (11.00 percent) were their sources of information. Shows are learned through mail (39.4 percent) and works sold are mainly through direct contact with buyers (36.36 percent).
Several recommendations are being made. It is suggested that (1) visual artists be treated as professionals; (2) practical information on competitions, opportunities, fellowships, and the like should be widely disseminated. (3) visual artists should be encouraged to attend seminars and/or conferences; (4) alumni should also be accommodated in libraries; and (5) linkages between institutions which cater to visual artists should be made even up to the extent of using electronic bulletin boards.
Computer print out.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Artists, Filipino; Information services--Philippines--Use studies; Special libraries--Philippines--Use studies